2009
DOI: 10.4100/jhse.2009.42.02
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical factors to be taken into account to prevent injuries and improve sporting performance on artificial turf

Abstract: This article reviews existing knowledge concerning the epidemiology, instruments and regulatory criteria currently used to evaluate artificial turf soccer pitches. Recent years have seen tremendous growth in the use of artificial turf as a playing surface for sports (rugby, soccer, American football…) and the problems traditionally associated with artificial turf and its relationship with a higher percentage of injuries seem to be disappearing. The contribution of biomechanics to the development of new techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…The present findings showed that agility performance, especially sprinting and turning, is better on AT than on NT. It matches the biomechanical relationship of the increase in fiction and decrease in impact absorption, which is the power produced from the subjects with AT which does not have the irregularities that NT has (Pérez Soriano et al, 2009) no matter whether players are carrying the ball or not. Therefore, when the athletes run on AT with sprinting and turning, they can run more smoothly than on NT.…”
Section: Overall Agility Performancesupporting
confidence: 61%
See 2 more Smart Citations
“…The present findings showed that agility performance, especially sprinting and turning, is better on AT than on NT. It matches the biomechanical relationship of the increase in fiction and decrease in impact absorption, which is the power produced from the subjects with AT which does not have the irregularities that NT has (Pérez Soriano et al, 2009) no matter whether players are carrying the ball or not. Therefore, when the athletes run on AT with sprinting and turning, they can run more smoothly than on NT.…”
Section: Overall Agility Performancesupporting
confidence: 61%
“…of natural turf (NT) (Fuller et al, 2010) at both competitive and recreational levels (Felipe et al, 2013). The development of artificial turf (AT) started in the 1960s (Pérez Soriano et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sur un terrain de type synthétique, il est de 38,2 par 1000 heures de jeu [41] (Tableau 3). La plupart des blessures se produisant sur le gazon artificiel serait associée à l'adaptation des mouvements sur des surfaces dures, avec une augmentation de l'activité musculaire excentrique et une modification des habitudes de déplacement dans le genou et la cheville [42]. De plus, avec des surfaces artificielles, les forces de traction sont supérieures et les joueurs peuvent acquérir une plus grande vitesse [42].…”
Section: Type De Terrainunclassified
“…This effect has been seen in soccer and football fields. Perez-Soriano et al 26 describe testing for other characteristics of playing surfaces that need to be considered in addition to the impact attenuation of the field. These studies build on earlier work showing that artificial surfaces can experience hard wear and levels of play exceeding what can be done on natural surfaces.…”
Section: Introductionmentioning
confidence: 99%